2021
DOI: 10.1007/s10639-021-10580-6
|View full text |Cite
|
Sign up to set email alerts
|

The configurational effects of task-technology fit, technology-induced engagement and motivation on learning performance during Covid-19 pandemic: An fsQCA approach

Abstract: At the onset of 2020, Covid-19 pandemic began and disrupted teaching and learning activities with substantial implications for resources and operations. Against this backdrop, the configural causal effects of task-technology fit, technology-induced engagement and motivation, gender, and residential location on learning performance are examined. The proposed association was tested with a dyad sample of faculty members and students (n = 16) using fuzzy sets (fsQCA) analysis. Results show that (i) task-technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…This technique asserts its dominance over PLS‐SEM in four unique ways. One , fsQCA can operate and generate quality results with small samples (Elçi & Abubakar, 2021). Two , fsQCA is grounded in complexity theory concerning examining complex and non‐linear relationships (Fiss, 2011; Kaya et al, 2020).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique asserts its dominance over PLS‐SEM in four unique ways. One , fsQCA can operate and generate quality results with small samples (Elçi & Abubakar, 2021). Two , fsQCA is grounded in complexity theory concerning examining complex and non‐linear relationships (Fiss, 2011; Kaya et al, 2020).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…An outcome's occurrence or emergence can be dictated by multiple sufficient conditions. The study variables were rescaled and transformed into full membership, cross‐over, and full non‐membership using the following anchors: six, four, and two for seven‐point scales and four, three, and two for five‐point scales based on guidelines from past studies (Elçi & Abubakar, 2021; Fiss, 2011; Shamout, 2020c). Full membership = 1, cross‐over point = 0.5, and full non‐membership = 0 in fuzzy sets.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…In their study about online teaching/learning experiences during the COVID-19 pandemic, Mishra et al [ 9 ] found that those faculty skilled in using social media apps such as Facebook, Twitter, and Instagram had relatively smoother transitions to using the online educational platforms for classes. Elci & Abubakar [ 49 ] pointed to the importance of the task-technology fit in supporting users to perform coursework during the COVID-19 pandemic. For many students, learning and studying from home can be much harder than learning and studying on campus.…”
Section: Related Literaturementioning
confidence: 99%
“…Many leisure and learning interactions were digitalized during the pandemic; thus, consumers have embraced a variety of digital forms ( Wang et al, 2021 ). The TTF model is an important model for studies of the effect of online experiences, such as technology-facilitated student learning activities ( Lçi and Abubakar, 2021 ). However, the characteristics of the two main factors in the TTF model, technologies and tasks, have changed during the past 2 years of the pandemic ( Wu et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%